Template-free synthesis of multiple-shell MgO/Pt hollow spheres as enhanced electrocatalysts. Issue 22 (19th May 2016) - Wang, Tao; Cui, Weihao; Peng, Meiling; Ouyang, Shenshen; Wang, Sheng
Abstract : MgO/Pt multiple-shell hollow sphere was fabricated using a template-free strategy and it exhibited enhanced electrocatalytic activity and long-term stability towards the oxidation reaction of methanol. Abstract : In general, most carbon-based hollow spheres with porous structures are prepared using the so-called hard-template method. In this paper, we present a template-free strategy for the fabrication of multiple-shell MgO/Pt hollow spheres. The as-prepared MgO/Pt spheres have a highly porous and self-supporting structure with a high surface area of 16.7 m 2 g −1 . Moreover, our research indicates that the as-prepared multiple-shell MgO/Pt hollow spheres exhibit enhanced electrocatalytic activity and long-term stability towards the oxidation reaction of methanol.